THE ROLE OF INTERNALIZATION OF RELIGIOUS VALUES IN THE FORMATION OF EMPLOYEE WORK ETHOS AT PT BAKRIE SUMATERA UTARA PLANTATION TBK - Putra, Azrin Eka; Rubino, Rubino; Indra, Farhan (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2025)
This study aims to reveal the role of internalization of religious values on the formation of employee work ethic at PT Bakrie Sumatera Utara Plantation Tbk. With a qualitative approach and phenomenological method, this research deeply explores the subjective experiences of employees through interviews, observations, and documentation of religious activities. The main focus is how Islamic values internalized through programs such as routine recitation, congregational prayers, and spiritual lectures shape Islamic work attitudes and behaviors. The results show that the process of internalizing religious values is carried out gradually and consistently, both through formal and informal approaches, and has the support of management and internal company religious leaders. The main findings show that values such as discipline, responsibility, honesty, and the spirit of togetherness began to materialize in employee work behavior. The work environment that previously tended to be individualistic has become more harmonious, collaborative, and worship-oriented. Thus, the internalization of religious values is proven to make a significant contribution in improving a productive and integrative Islamic work ethic. This study recommends that companies continue to strengthen religious programs and expand spiritual approaches into the sharia-based human resource management system.